Sorption of copper (ii) and nonionic surfactant by ion exchangers and activated carbon - Jancevičiūtė, Renata; Gefenienė, Audronė (Journal of Environmental Engineering and Landscape Management, 2006)
Ion exchange resins, which are widely used for the removal of copper (II) ions from effluents, can also sorb nonionic surfactants entering into the wastewater with copper (II) ions simultaneously after various industrial processes. The study of equilibrium sorption of copper (II) and nonionic surfactant Lutensol AO‐10 under laboratory conditions by different types of ion exchangers and activated carbon has shown that the Purolite S950 chelating ion exchanger has the highest sorption capacity for copper (II) ions. Ion exchangers with carboxylic functional groups demonstrate the highest affinity for nonionic surfactant. Purolite C107E weak acid cation exchanger could be suitable for the cosorption of copper (II) ions and nonionic surfactant Lutensol AO‐10. Kinetic study of this ion exchange resin leads to a conclusion that the sorption of copper (II) ions was a fast process, and after 30 min the equilibrium was attained. When the concentration of copper (II) solution decreases, difference between the sorption capacity of various ion exchangers decrease. The influence of nonionic surfactant on the sorption of copper (II) is insignificant. Cu (II) jonų ir nejoninių paviršinio aktyvumo medžiagų (PAM) sorbcija jonitais ir aktyvintąja anglimi Santrauka. Jonitai, plačiai naudojami vario (II) jonams iš nuotekų šalinti, gali sorbuoti ir nejonines paviršinio aktyvumo medžiagas (NPAM), kurios neretai patenka į nuotekas po įvairių gamybinių procesų kartu su vario jonais. Laboratorinėmis sąlygomis tiriant pusiausvirąją vario jonų ir NPAM Lutensol AO-10 sorbciją įvairių tipų jonitais ir aktyvintąja anglimi buvo nustatyta, kad didžiausia geba sulaikyti vario jonus būdinga chelatiniam jonitui Purolite S950. Didžiausias giminingumas nejoninei PAM būdingas karboksiliniams katijonitams. Bendrai vario (II) jonų ir NPAM sorbcijai geriausiai tiktų silpnai rūgštinis katijonitas Purolite C107E. Kinetiniai šio jonito tyrimai leidžia daryti išvadą, kad vario jonų sorbcija vyksta greitai, ir pusiausvyra nusistovi per 30 min. Mažėjant vario jonų koncentracijai tirpale skirtumai tarp įvairių jonitų sorbcinės gebos mažėja. Nejoninės PAM Lutensol AO-10 įtaka vario jonų sorbcijai yra nežymi. Reikšminiai žodžiai: jonitas, aktyvintoji anglis, sorbcija, varis, nejoninė paviršinio aktyvumo medžiaga (NPAM), išvalymo laipsnis. Сорбция меди (ii) и неионных поверхностно-активных веществ с помощью ионитов и активированного угля Резюме. Иониты, широко используемые для устранения ионов меди (II) из сточных вод, способны сорбировать и неионные поверхностно-активные вещества (НПАВ), которые после многих производственных процессов переходят в сточные воды совместно с ионами меди (II). Исследования равновесной сорбции меди (II) и НПАВ с помощью разных типов ионитов и активированного угля в лабораторных условиях показали, что наивысшей сорбционной емкостью отличается хелатный ионит Purolite S950. Наивысшим сродством к НПАВ отличаются карбоксильные катиониты. Наиболее приемлемым ионитом для совместной сорбции меди (II) и НПАВ можно считать слабокислотный катионит Purolite C107E. Исследование кинетики сорбции меди (II) этим катионитом показало, что сорбция меди (II) отличается быстротой, и равновесие достигается в течение 30 минут. При снижении концентрации меди (II) в растворе различия между сорбционной емкостью разных ионитов снижаются. Установлено, что влияние НПАВ на сорбцию меди (II) незначительно. Ключевые слова: ионит, активированный уголь, сорбция, неионное поверхностно-активное вещество, медь, степень очистки. Firstd Published Online: 14 Oct 2010